Identification and characterization of a novel Cytorhabdovirus associated with goji berry (Lycium barbarum L.) crinkle disease - Wang, Rong; Liu, Sai; Xu, Changqing; Yu, Jing; Wei, Jianhe; Ding, Wanlong; Li, Yong (Frontiers in Microbiology, 2024)
Goji berry (Lycium barbarum L.) is a traditional Chinese herbal medicinal plant that is extensively cultivated in the arid and semiarid regions of northwest China. In this study, a novel cytorhabdovirus, tentatively named "goji cytorhabdovirus A (GCVA)", was identified from the goji berry plant exhibiting leaf crinkle symptoms through high-throughput sequencing (HTS). GCVA contains a linear, negative sense single-stranded RNA genome of 14,812 nucleotides and encodes six open reading frames in the order of 3′ leader-N-P-P4-M-G-L-5′ trailer. The genome of GCVA shares the highest nucleotide (nt) identity of 65.80% (16% query coverage) with yerba mate virus A (YmVA) (NC_076472). The N and L proteins also share low amino acid (aa) identities (<35.42% and <41.23%, respectively) with known cytorhabdoviruses. Typical features of the viruses in the genus Cytorhabdovirus include a highly conserved consensus sequence in the intergenic regions and extensive complementation of the 5′ non-coding trailer and the 3′ leader. These features were also found in GCVA. These data in combination with a phylogenetic analysis that was based on the aa sequences of the N and L proteins support the proposal that GCVA is a new species in the genus Cytorhabdovirus.